Mathematics
aubiefan480
26

Solve the system by substitution. 6x + 3y = -6 2x + y = -2

+2
(2) Answers
AmyMorris

Solutions  First Lets solve for this equation [latex]6x + 3y = -6 [/latex]  [latex]6x + 3y = -6 [/latex]  [latex]6x+3(-2-2x)=-6 [/latex]  [latex]-6=-6[/latex]  Therefore this given equation is a dependent system.  Solve for [latex]2x + y = -2[/latex]  [latex]2x+y=-2[/latex]  [latex]y=-2-2x [/latex]  There are too many solutions to these equations. 

Georgey

6x + 3y = -6 2x + y = -2 Solve both equations for the same variable, in this case, I'll solve for y. 2x + y = -2   Subtract 2x from both sides y = -2x -2 6x + 3y = -6         Subtract 6x from both sides         3y = -6x -6   Divide both sides by 3           y = -2x -2   Once you have them solved you can set them equal to each other and solve. -2x -2 = -2x -2  But, these two equations are the same, so any number you put in for x will work. The answer to the system is infinite solutions.

Add answer